2008
DOI: 10.1016/j.molcel.2008.03.023
|View full text |Cite
|
Sign up to set email alerts
|

Colocalization of Sensors Is Sufficient to Activate the DNA Damage Checkpoint in the Absence of Damage

Abstract: Previous work on the DNA damage checkpoint in Saccharomyces cerevisiae has shown that two complexes independently sense DNA lesions: the kinase Mec1-Ddc2 and the PCNA-like 9-1-1 complex. To test whether colocalization of these components is sufficient for checkpoint activation, we fused these checkpoint proteins to the LacI repressor and artificially colocalized these fusions by expressing them in cells harboring Lac operator arrays. We observed Rad53 and Rad9 phosphorylation, Sml1 degradation, and metaphase d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

11
168
2
3

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 153 publications
(188 citation statements)
references
References 70 publications
11
168
2
3
Order By: Relevance
“…The importance of a specific protein-protein association in DNA damage checkpoint signaling is further revealed by the observations that a forced assembly of signaling proteins to the same location in the genome could activate Rad53 without introducing DNA damage signals (41,42). In addition, many proteins are known to localize to the site of DNA damage in cells (43).…”
Section: Discussionmentioning
confidence: 99%
“…The importance of a specific protein-protein association in DNA damage checkpoint signaling is further revealed by the observations that a forced assembly of signaling proteins to the same location in the genome could activate Rad53 without introducing DNA damage signals (41,42). In addition, many proteins are known to localize to the site of DNA damage in cells (43).…”
Section: Discussionmentioning
confidence: 99%
“…The activation of Mec1-Ddc2 (ATR-ATRIP in mammals) is regulated by a number of factors: First, Mec1 signaling is dependent on colocalization of the Mec1-Ddc2 with the PCNA-like 9-1-1 Ddc1-Rad17-Mec3 complex (RAD9-RAD1-HUS1, in mammals) (Parrilla-Castellar et al 2004;Bonilla et al 2008). Second, it has been reported that the yeast 9-1-1 complex can activate Mec1 directly in vitro (Majka et al 2006).…”
mentioning
confidence: 99%
“…The generation of single-stranded DNA coated with the single-stranded binding protein RPA 3 is a critical step in the recruitment of Mec1 to sites of damage, which is mediated through Ddc2-RPA interactions (4,5). One or more Mec1 activators are also recruited to these sites, and the juxtaposition on chromatin of a given activator with Mec1 results in the activation of Mec1 protein kinase activity (6) and the phosphorylation of a large number of proteins, including RPA, subunits of the 9-1-1 checkpoint clamp, mediator proteins, and downstream effector kinases such as Rad53.…”
mentioning
confidence: 99%